Comparison of Clipped Laparoscopic Cholecystectomy and Clipless Laparoscopic Cholecystectomy in Context of Biliary Leakage - Aurangzeb Khan, Zulfiqar Ali Shar, Munawer Latif Memon, Abdul Rasheed Zai, Sadaf Chandio, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the outcome of clipped laparoscopic cholecystectomy and clipless laparoscopic cholecystectomy in context of biliary leakage. Study Design: Cross-sectional analytical study Place and Duration of Study: Department of Surgery Unit-II, Benazir Bhutto Hospital Rawalpindi from 1st September 2021 to 31st August 2022. Methodology: One hundred and twenty patients were included in the study and divided into two major groups. The biochemical analysis and ultrasonography was performed post 8 hours fasting. Group one had those cases which underwent clipped laparoscopic cholecystectomy while group 2 had those cases which underwent clipless laparoscopic cholecystectomy. The age of the patients was selected between 40 to 60 years and the prevalence for this sampling was considered as 20% in Pakistan. The demographic details, clinical history, signs and symptoms, clinical diagnosis based on USG, lipid profiling, and variables as post-operative time, hospital stay and ease in procedure were documented. Results: The mean age of the cases underwent clipped laparoscopic cholecystectomy was 42.3±12.11year with 40 females and 20 males who underwent those procedures. The mean age of the cases underwent clipless laparoscopic cholecystectomy was 40±11.05 years with 45 females and 15 males. The present study results evidently highlighted the fact that there were high percentage cases of biliary leakage seen in clipped cases than in the clipless cases. There were22 cases with 36.6% in clipped groups while 9 cases with biliary leakage such as 15% in clipless group. Conclusion: Clipless laparoscopic cholecystectomy is a better optional procedure with efficient usefulness in context to biliary leakage, operation time and hospital stays. Keywords: Outcome, Clipped laparoscopy cholecystectomy, Clipless laparoscopic cholecystectomy, Biliary leakage